Respiratory metapneumoviral infection without co-infection in association with acute and chronic lung allograft dysfunction - Dosanjh A (Dove Medical Press, 2015)
Amrita DosanjhDepartment of Pediatrics, Rady Children’s Hospital, San Diego, CA, USABackground: Metapneumoviral respiratory infection is a community-acquired respiratory viral (CARV) infection. Lung transplantation recipients exposed to CARV are at risk for development of allograft rejection. The cellular and molecular pathways initiated by viral infection leading to allograft dysfunction are not completely understood. The aim of this study was to identify human metapneumoviral (hMPV) cases in association with allograft rejection.Methods: A literature search was conducted to identify cases of both hMPV and allograft rejection within 6 months of the initial infection. This resulted in 1,007 lung transplantation recipients, with a total of 2,883 samples identified. Of these, 57 demonstrated isolated hMPV without co-infection with other agents.Results: The results of the study indicate that 35% of acute hMPV infections without co-infection, at the time of detection by molecular diagnostic platforms, were associated with acute cellular rejection within 3 months. There were 9.4% of the cases subsequently associated with chronic allograft dysfunction/bronchiolitis obliterans syndrome, which was collectively termed chronic rejection for purposes of analysis. In conclusion, the prompt identification of isolated hMPV from lung transplantation patients is an important treatable risk factor for subsequent allograft dysfunction. The cellular and molecular pathogenesis of viral-induced allograft rejection remains a topic of future study.Keywords: viral infection, bronchiolitis obliterans, acute cellular rejection, allograft, lung, metapneumovirus